The effect of eye-hand coordination on self-confidence levels among indoor volleyball referees - Subarna, Subarna; Tangkudung, James; Asmawi, Moch (Journal of Education, Health and Sport, 2019)
This study was aimed to examine the effect of eye-hand coordination on the self-confidence level of indoor volleyball referees in West Java, Indonesia. It applied descriptive research to describe the characteristics of a particular population in this case referees being studied. This study took place in two sports tournaments named PORDA (Regional Sports Week Competition) XIII and Kejurda qualifying rounds among volleyball clubs in West Java in October 2017. To achieve the objective of this study, a survey method with measurement techniques and test were applied. The population involved in this study were 22 referees assigned to lead games in PORDA XIII and Kejurda qualifying round among clubs in west java in 2018 and 2017 respectively. To obtain a sample, this study applied the total sampling technique where all respondents were examined.. Referees’ self-confidence level was collected using questionnaire whereas eye-hand was measured using motor fitness test instrument. Motor fitness test required referees to throw the ball to the target or volleyball referee who acted as research respondent. When it came to data analysis, path analysis technique was used to both examine the relationship between research variables and measure the direct and indirect effect of one variable on another variable. The results show that referees’ self- confidence level in this study for each indicator fell into the excellent category. Their ability to perform motor test can be described as good. This study shows that there was a positive and significant effect of referees’ eye-hand coordination ability on the level of their self-confidence level in carrying out their duties in leading a match.